2017
DOI: 10.1007/s40266-017-0462-x
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss in Patients with Dementia: Considering the Potential Impact of Pharmacotherapy

Abstract: Unintentional body weight loss is common in patients with dementia and is linked to cognitive impairment and poorer disease outcomes. It is proposed that some dementia medications with market approval, while aiming to improve cognitive and functional outcomes of a patient with dementia, are associated with reported body weight or body mass index loss. This review presents evidence in the published literature on body weight loss in dementia, describes selected theories behind body weight loss, evaluates the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 168 publications
2
26
0
3
Order By: Relevance
“…mesial temporal cortex) are affected during the preclinical dementia phase; and adipose tissue loss may result from preclinical apathy, reduced olfactory function, difficulty with eating (e.g., aphasia), inadequate nutrition or prescribed medicines targeting dementia related symptoms e.g. depression or cognitive impairments [46]. Furthermore, we found that the odds of developing dementia in elderly women were lower among those with intermediate blood leptin levels.…”
Section: Discussionmentioning
confidence: 71%
“…mesial temporal cortex) are affected during the preclinical dementia phase; and adipose tissue loss may result from preclinical apathy, reduced olfactory function, difficulty with eating (e.g., aphasia), inadequate nutrition or prescribed medicines targeting dementia related symptoms e.g. depression or cognitive impairments [46]. Furthermore, we found that the odds of developing dementia in elderly women were lower among those with intermediate blood leptin levels.…”
Section: Discussionmentioning
confidence: 71%
“…Unter diesem Blickwinkel ist auch die ungewollte Gewichtsabnahme bei PatientInnen mit Demenz zu beurteilen. Die Gewichtsabnahme ist zum Teil Bestandteil des Krankheitsbildes, zum Teil aber auch mit der antidementiellen Therapie assoziiert [14]. Der Zusammenhang von Körpergewicht und Demenz ist paradox: Adipositas im mittleren Alter erhöht das Risiko für eine spätere Demenz, aber ungewollte Gewichtsabnahme im höheren Lebensalter erhöht das Risiko für das Auftreten der milden kognitiven Einschränkung bzw.…”
Section: Definition Und Erläuterungenunclassified
“…Für die insbesondere in frühen Stadien der Alzheimer-Demenz eingesetzten Cholinesterase-Inhibitoren Donepezil, Rivastigmin und Galantamin ist das Risiko für ungewollte Gewichtsabnahme in einer Meta-Analyse mit 2,2 (95%-Konfidenzintervall von 1,5-3,2) beziffert worden, also wurde bei mit Cholinesterase-Inhibitoren behandelten PatientInnen doppelt so häufig ein Gewichtsverlust beobachtet als bei den mit Placebo behandelten PatientInnen [16]. Aufgrund der cholinergen Überstimulation anhaltende gastrointestinale Symptome scheinen hier maßgeblich beteiligt zu sein [14]. Auf Gewichtsänderungen von PatientInnen mit Demenz und Indikation zur Therapie oder unter bereits laufender Therapie mit einem Cholinesterase-Inhibitor ist also ein besonderes Augenmerk zu richten.…”
Section: Definition Und Erläuterungenunclassified
“…The complexity of AT endocrinology and related systems is well-illustrated by the range of medications used for vascular diseases of old age. Several of these medications differentially influence body weight [11,55] and subsequent blood lipid levels. In addition, studies of adults with cerebral small vessel disease or HIV-related adiposity syndromes allow continued evaluation of the aforementioned, co-occurring factors and partitioning out of different adiposity pathways [49,56,57].…”
Section: Endocrine Adipose Tissuementioning
confidence: 99%
“…Individuals with obesity, T2D, or heart failure have elevated levels of serum free fatty acids [84] that promote lipotoxicity of cardiomyocytes [85]; and profound changes in CLs' composition occur in T2D. Since the brain is approximately 60% fat [26] and obesity is associated with later-onset cognitive impairments and dementias [50,55,86], perhaps the abundance of these circulating lipid species is of multisystem pathological significance. This multisystem role of CL alterations contributing to mitochondrial dysfunction in particular makes them especially interesting [87].…”
Section: Lipidomicsmentioning
confidence: 99%